(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2018)
Considering the high prevalence of human cervical cancer and the adverse effects of the available treatments, it is important to develop studies involving plants. Eugenia uniflora L. is a Brazilian native plant widely used in folk medicine and some biological effects have already been described. In this study, we investigated the biologicals effects of the aqueous crude extract of E. uniflora leaves in relation to the viability of human cervical cancer cells (SiHa), non-tumorigenic cells HaCaT and human lymphocytes. Our results demonstrated that different concentrations of E. uniflora’s extract significantly inhibited the viability of the Siha cell line at 24, 48 and 72 hours of treatment, but did not induce significant changes in the HaCat cell line and human lymphocytes. Tumor cells had adhesion capacity, migration processes, ability of colony forming and the potential to recover its viability after treatment. withdrawal, significantly reduced. The nuclear morphology revealed chromatin condensation, and the flow cytometry showed predominantly cell death by apoptosis in the treated tumor cells. Therefore, the E. uniflora’s extract may contribute for future studies aiming at new therapeutic perspectives for human cervical cancer.